Pembentukan Personal Branding Arief Muhammad Sebagai Content Creator dan Entrepreneur di Media Sosial Instagram - Alifia, Nadya Putri; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium; Vol 4 No 1 (2023): Jurnal Ilmu Komunikasi Vol 4 No 1 Tahun 2023, 2023)
Personal branding is an image that is shown to the wider community, in other words, personal branding is a process of forming public perceptions of aspects that are owned by a person. Arief Muhammad as a content creator and entrepreneur uses social media  Instagram as a forum to create a personal brand. This study uses 8 (eight) laws of personal branding according to Peter F. Montoya. Arief Muhammad’s personal branding shows him as a creative and dynamic figure, with his creativity Arief does not limit himself and continues to move to develop himself in various aspects. In order to create personal branding with the eight laws according to Peter F. Montoya, as content creator The Law of Specialization, The Law of Personality, The Law of Distinctiveness is the most highlighted concept. And as an entrepreneur, The Law of Leadership and The Law of Persistence are the most stand out concept. Keywords : Personal Branding, Content creator, Entrepreneur, Instagram